Tensiomyography parameters and jumping and sprinting performance in Brazilian elite soccer players - Gil, S.; Loturco, I.; Tricoli, V.; Ugrinowitsch, C.; Kobal, R.; Cal Abad, C. C.; Roschel, H. (Sports Biomechanics, 2015)
Tensiomyography has been suggested as an indirect marker of muscle stiffness, which is associated with strength/power performance. Therefore, it is reasonable to suggest that tensiomyography parameters could be associated with power-related motor tasks. The purpose of this study was to investigate the association between tensiomyography parameters (from rectus and biceps femoris) and jumping and sprinting abilities in elite soccer players. In addition, we used tensiomyography parameters to compare the lateral symmetry between dominant and non-dominant legs. Twenty elite soccer players (age: 23.3 ± 4.8 years; height: 183.5 ± 6.6 cm; weight: 77.8 ± 7.5 kg) volunteered to participate in the study. Significant moderate negative correlations between biceps femoris displacement and contact time (r = -0.5, p = 0.03), rectus femoris displacement and contact time (r = -0.51, p = 0.02), and a significant moderate correlation between biceps femoris displacement and reactive strength index (r = 0.5, p = 0.03) were found. There were no correlations between tensiomyography parameters and power-related motor tasks. In addition, no differences in tensiomyography parameters between dominant and non-dominant legs were found. Our data suggest that tensiomyography parameters are not associated with power-related motor tasks performance in elite soccer players.